Workers, Firms and Task Heterogeneity in International Trade Analysis: An Example of Wage Effects of Trade Within GVC - Aleksandra Parteka; Joanna Wolszczak-Derlacz (Entrepreneurial Business and Economics Review, 2017)
Objective: The main aim of this article is to present how the heterogeneity of workers, firms, and tasks can be incorporated into empirical international trade analysis. In particular, we provide an empirical example in which we aim to quantify the reliance on foreign value added (FVA) within Global Value Chains (GVC) on wages.